Agronomic performance and nutritional profiling of Theobroma grandiflorum (cupuassu) clones under colombian amazon conditions - Velasquez-Vasconez, Pedro Alexander; Castro, María Isabel; Criollo, Dagoberto; Diaz, Esteban; Zambrano , Juan Carlos (Revista de Ciencias Agrícolas, 2026)
Theobroma grandiflorum (cupuassu) is an Amazonian fruit tree of increasing importance for agro-industrial development in Colombia due to its nutritional value and multiple commercial applications. However, its cultivation still faces limitations due to insufficient knowledge regarding the adaptability and productivity of its genotypes under local conditions. This study aimed to evaluate eight genotypes over a three-year period in an experimental field located in Florencia, Caquetá, Colombia. The trial was established as a monoculture of trees with a repeated-measures design. Data included productive variables (fruit number, weight, pulp, and seed yields) and nutritional composition (minerals, fatty acids, and bromatological parameters). The analysis of variance (ANOVA) and Duncan’s test revealed significant differences (p < 0.05) among the genotypes, with UNR146 and UNR153 excelling in pulp yield (29.00 kg and 29.97 kg, respectively) and almond yield (12.92 kg and 14.81 kg, respectively). These two genotypes showed a superior number of fruits per tree (65 and 71, respectively), positively influencing total almond and pulp production. Furthermore, UNR146 and UNR153 demonstrated consistent performance across three consecutive years of evaluation, outperforming other genotypes, particularly in almond and pulp yield. Their high productivity is coupled with favorable mineral and fatty acid profiles, with UNR153 achieving the highest almond yield at 14.8 kg per plant. Principal component analysis revealed key relationships between minerals and fatty acids, highlighting differences in pulp and seed quality. Clones UNR146 and UNR153 exhibit strong genetic potential to improve cupuassu yield and quality under tropical conditions in the Colombian Amazon.